Theorizing lesson study: Integration of action research methodology in Japanese lesson study approach - Ibadullayeva, N.S. (Karagandy University of the name of acad. E.A. Buketov, 2024)
Global challenges faced by teacher researchers outside of Japan are related to theoretical, practical knowledge, research methodology, success and sustainability of adapted lesson study (LS) projects. These issues highlight the necessity of in-depth theoretical research of authentic Japanese lesson study (JLS) approach. The purpose of the article is to explore LS theorization through theoretical analysis of multifaceted structure of JLS components and integration of action research (AR) methodology in JLS to make LS evidence-based and comprehensible. The main idea is theorization of LS through modeling, evaluation checklist and conceptualization of LS philosophy. As a result of comparative, analysis and synthesis, structured analysis and modeling research methods, multi cyclical LS model integrated with AR methodology, evaluation checklist used as assessment tool for model realization and LS philosophy were developed. The model and checklist are used to describe 4 LS as AR stages (pre-diagnostic, intervention, post-diagnostic and knowledge construction) and 37 components. The model is significant to get theoretical knowledge acquisition, the evaluation checklist is crucial in practice as self-correction, self-assessment and self-regulation tool. They can be utilized by teachers throughout LS process. The research findings contribute to developing LS methodology with a set of assessment criteria to make LS scientifically grounded research.
Global challenges faced by teacher researchers outside of Japan are related to theoretical, practical knowledge, research methodology, success and sustainability of adapted lesson study (LS) projects. These issues highlight the necessity of in-depth theoretical research of authentic Japanese lesson study (JLS) approach. The purpose of the article is to explore LS theorization through theoretical analysis of multifaceted structure of JLS components and integration of action research (AR) methodology in JLS to make LS evidence-based and comprehensible. The main idea is theorization of LS through modeling, evaluation checklist and conceptualization of LS philosophy. As a result of comparative, analysis and synthesis, structured analysis and modeling research methods, multi cyclical LS model integrated with AR methodology, evaluation checklist used as assessment tool for model realization and LS philosophy were developed. The model and checklist are used to describe 4 LS as AR stages (pre-diagnostic, intervention, post-diagnostic and knowledge construction) and 37 components. The model is significant to get theoretical knowledge acquisition, the evaluation checklist is crucial in practice as self-correction, self-assessment and self-regulation tool. They can be utilized by teachers throughout LS process. The research findings contribute to developing LS methodology with a set of assessment criteria to make LS scientifically grounded research.
Keywords: Japanese lesson study; action research; lesson study as action research; lesson study philosophy; action research methodology; lesson study model; lesson study components; Theorizing; lesson study; Теоретизирование подхода; интеграция методологии; методология Action Research; японский подход; японский подход Lesson Study; японский подход исследования урока; модель Lesson Study; компоненты Lesson Study; философия Lesson Study; исследование урока в контексте исследования в действии; исследование в действии; Lesson Study моделi; Lesson Study компоненттері; жапондық сабақты зерттеу үдерiсi; iс-әрекеттегi зерттеу; Action Research әдіснамасы; Lesson Study философиясы; сабакты зерттеу контексіедегі iс-әрекеттегi зерттеу